Pengaruh Profitabilitas dan Kebijakan Hutang Terhadap Nilai Perusahaan di Perusahaan Manufaktur Sektor Barang Konsumsi Yang Terdaftar di BEI Tahun 2022 - Siti Fitriah Muflihah (PT Maju Malaqbi Makkarana, 2023)
The purpose of this research is to find out how the effect of profitability and debt policy on firm value in manufacturing companies in the consumer goods sector are listed on the Indonesian stock exchange. The data collection technique in this study was by using secondary data (indirect data sources), library research and documentation. The method used in this study is a quantitative descriptive method. The analytical tool used is to use the formula Return on Assets (ROA), Debt to Equity Ratio (DER) and Price to Book Value (PBV). Based on the results of the study indicate that simultaneously Profitability and Debt Policy have a significant effect on Firm Value. And Partially Profitability has no significant effect on Firm Value and Debt Policy has a significant effect on Firm Value.